Process simulation of wet compression moulding for continuous fibre-reinforced polymers - Poppe, Christian Timo (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
Interdisciplinary development approaches for system-efficient lightweight design unite a comprehensive understanding of materials, processes and methods. This applies particularly to continuous fibre-reinforced plastics (CoFRPs), which offer high weight-specific material properties and enable load path-optimised designs. This thesis is dedicated to understanding and modelling Wet Compression Moulding (WCM) to facilitate large-volume production of CoFRP structural components.